Nationalist elites, Irish voters and Irish political-development - comparative perspective - Garvin, Tom (Economic & Social Studies, 1977)
In this essay it is argued that the Irish political system, although it is usually seen as a deviant case among Western polities, is best viewed in a broader comparative perspective - that of decolonialising political systems. In the central sections o f this paper an examination is made of the development of the Irish party system and it is concluded that the structure of the system tallies well with common descriptions o f the politics of post-colonial states. It is also suggested that the main significant exception to this general statement is afforded by the governmental machine, which has remained intact and centralised rather than becoming decentralised and penetrated by politics in the manner typical of democratic post-colonial countries. In a final section, it is suggested that certain well-known peculiarities of Irish political culture are to be explained with reference to this characteristically Irish divorce between politics and government.
Keywords: Politics; Ireland